A Star is Born - Cooper, Bradley; Lady Gaga; Elliott, Sam, 1944-; Clay, Andrew Dice (Burbank, CA : Warner Bros. Entertainment, 2019)
A musician helps a rising singer find fame as his own career begins a downward spiral.
Rental ready.
Remake of the 1954 film of the same title.
Wide screen 1.66:1.
Lady Gaga, Bradley Cooper, Sam Elliott, Andrew Dice Clay, Rafi Gavron.
MPAA rating: R.
Keywords: Musicians -- Drama; Singers -- Drama; Man-woman relationships -- Drama; Romance films; Musical films; Film remakes; Fiction films; Feature films